Overview of the Selected EU Textiles Policy Initiatives: Self-Stand Sustainable Game Changers or ‘Palliative’ Half-Measures - Korchahin, Dmytro (Teisė, 2024)
The present paper seeks to provide regulatory insights concerning the fundamental nature of the selected EU textile policy initiatives and ignite further debate regarding their enhancement. The author of the article analyses the selected EU textile policy initiatives, spots their main defect along with additional shortcomings, proposes optimisation measures, and starts a new debate on the future of textile regulation from the consumer side. The author concludes that the analysed EU proposals are detailed and innovative; however, they have numerous shortcomings that, if optimised, might enhance the current regulatory value of the analysed proposals. Besides, the author concludes that the debate should be started to tackle not only the industry side but also regulate the consumer side to actually aim the legislation at sustainable development and not only at environmental harm reduction, which would enhance the future regulatory value of the said proposals.
Keywords: textile regulation; harm reduction; circular economy; environment; EU policy; sustainable fashion; fast fashion